1997
DOI: 10.1002/(sici)1097-0215(19971210)73:6<786::aid-ijc2>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr-virus-associated gastric cancer in Russia

Abstract: The present investigation was carried out to estimate the prevalence of EBV‐associated cases among gastric carcinoma (GC) patients of Russia and the Republics of the former Soviet Union (FSU). With this aim, formalin‐fixed paraffin‐embedded blocks from 206 gastric carcinomas obtained from patients of the Cancer Research Center, Moscow, were investigated by EBV‐encoded RNA‐1 (EBER‐1) in situ hybridization applied to paraffin sections. As a result, 18 GC cases (8.7%) revealed uniform EBER‐1 expression restricted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
1
6

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 13 publications
5
30
1
6
Order By: Relevance
“…41 Male predominance was one of the most evident clinicopathologic features of EBV-associated GC demonstrated in previous studies. 10,11,16,40 Although we also found male predominance in the present study, the gender ratio (male/female) was merely 1.9, which did not achieve statistical significance, and was lower than the gender ratios reported elsewhere. Although most of the studies reported so far showed male predominance, a notable exception is the finding reported in Mexico by Herrera-Goepfert et al 41 In that study the male/female ratio was 1.1.…”
Section: Factors Associated With Ebv Positive Casescontrasting
confidence: 96%
See 3 more Smart Citations
“…41 Male predominance was one of the most evident clinicopathologic features of EBV-associated GC demonstrated in previous studies. 10,11,16,40 Although we also found male predominance in the present study, the gender ratio (male/female) was merely 1.9, which did not achieve statistical significance, and was lower than the gender ratios reported elsewhere. Although most of the studies reported so far showed male predominance, a notable exception is the finding reported in Mexico by Herrera-Goepfert et al 41 In that study the male/female ratio was 1.1.…”
Section: Factors Associated With Ebv Positive Casescontrasting
confidence: 96%
“…This frequency is significantly higher (p Ͻ 0.001) than that reported of in other countries like Japan, Russia and Mexico, where it ranges between 8.1-10% (Table III). 11,16,41 Conversely, the frequency of EBV-associated GC in the middle or antrum in our study were similar to that reported of in these countries (Table III).…”
Section: Factors Associated With Ebv Positive Casessupporting
confidence: 90%
See 2 more Smart Citations
“…Meanwhile, we have applied this screening method to an additional 82 randomly selected cases, and observed an overall EBV positivity of 7.7% in a total of 324 cases from 19 different Dutch hospitals (data not shown). This is in agreement with the current literature concerning the prevalence of EBV-carrying gastric adenocarcinomas worldwide (7,9,29,30).…”
Section: Discussionsupporting
confidence: 93%